Review of Public Health Expenditure in the Republic of Tajikistan : Discussion Paper - Neelsen, Sven; Egamov, Farrukh; Dorgabekova, Husniya; Madeville, Kate (World Bank, Washington, DC, 2021)
This Public Expenditure Review updates previous assessments of the levels and efficiency of health financing in Tajikistan and its consequences for healthcare access and health of the Tajik population. Funding for the public healthcare system which provides almost all healthcare remains far short of levels required to provide a universal basic benefit package. As a result, household out-of-pocket payments account for most healthcare spending in the country, and Tajiks frequently forgo needed care for financial reasons. The underfunding of public healthcare in part results from an overall lack of public revenues. It is, however, exacerbated by the health sector enjoying limited priority, with a health share in total government spending far below internationally recognized targets. Inefficiencies in the spending of the limited public funds further undermine the system’s ability to provide the population with basic healthcare of appropriate quality. Despite efforts in the past two decades to introduce elements of strategic purchasing and direct a higher share of funding towards primary care, public health financing in Tajikistan still largely follows the centrally planned, hospital-focused, and mainly input-financed Semashko model. The result are substantial regional inequalities in per capita government health spending which reflect differences in health facility and health worker densities rather than healthcare need, a continued overemphasis on hospital and specialist care, and an inability of facility managers to take efficiency-oriented staffing decisions. Key recommendation to address these shortcoming are that a substantially higher share of public revenues be allocated to the health sector, that an independent, single payer organization, a fully-fledged capitation mechanism for primary care and elements of strategic purchasing for inpatient care be gradually introduced, and that current benefit packages are revised and extended to achieve more rational and equitable healthcare utilization. Broad consensus building among stakeholders will be essential for the success of such reforms.